STRATEGI MANAJEMEN SDM BERBASIS KOMPETENSI UNTUK MENINGKATKAN MUTU PENDIDIKAN - Intan Purnama Sari (Ensiklopedia Research and Community Service Review, 2026)
Higher education plays a strategic role in producing qualified, competitive, and adaptive human resources (HR) in response to global changes. One of the key determinants of higher education quality improvement is effective human resource management oriented toward competency development. This study aims to analyze in depth the competency-based human resource management (HRM) strategy and its contribution to improving education quality at Universitas Dharma Indonesia. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and document analysis involving university leaders, HR managers, lecturers, and administrative staff selected through purposive sampling. Data analysis was conducted using the stages of data reduction, data display, and conclusion drawing, supported by triangulation techniques to ensure data credibility. The findings indicate that the competency-based HRM strategy at Universitas Dharma Indonesia is implemented through systematic HR planning, competency-based recruitment and selection, continuous training and development programs, and performance appraisal integrated with career development. The implementation of this strategy positively contributes to the improvement of lecturers’ and staff competencies, the quality of the learning process, professional performance, and the effectiveness of academic services. Furthermore, the impact of competency-based HRM implementation is reflected in enhanced education quality and increased student satisfaction. This study concludes that competency-based human resource management is a strategic and effective approach to supporting quality improvement in higher education. The results of this study are expected to provide both theoretical and practical contributions for higher education institutions in formulating sustainable and quality-oriented HR management policies.Keywords: human resource management; competency-based; education quality; higher education; case study